Virtual consolidation of Boston's Beth Israel and New England Deaconess Hospitals via the World Wide Web. - Halamka, J. D. (American Medical Informatics Association, 1997)
With the advent of Integrated Healthcare Delivery Systems, medical records are increasingly distributed across multiple institutions. Timely access to these medical records is a critical need for healthcare providers. The CareWeb project provides an architecture for World Wide Web-based retrieval of electronic medical records from heterogeneous data sources. Using Health Level 7 (HL7), web technologies and readily available software components, we consolidated the electronic records of Boston's Beth Israel and Deaconess Hospitals. We report on the creation of CareWeb (freya.bidmc.harvard.edu/careweb.htm) and propose it as a means to electronically link Integrated Health Care Delivery Systems and geographically distant information resources.